A view from the Greek side - Ekroth, Gunnel (Journal of ancient Judaism, 2016)
This paper addresses the animal bone material from ancient Qumran, from the comparative perspective of zooarchaeological evidence recovered in ancient Greek cult contexts. The article offers an overview of the paramount importance of animal bones for the understanding of ancient Greek religion and sacrificial practices in particular, followed by a review of the Qumran material, taking as its starting point the zooarchaeological evidence and the archaeological find contexts. The methodological complications of letting the written sources guide the interpretation of the archaeological material are explored, and it is suggested that the Qumran bones are to be interpreted as remains of ritual meals following animal sacrifices, as proposed by Jodi Magness. The presence of calcined bones additionally supports the proposal that there was once an altar in area L130, and it is argued that the absence of preserved altar installations in many ancient sanctuaries cannot be used as an argument against their ever having been present. Finally, the similarities between Israelite and Greek sacrificial practices are touched upon, arguing for the advantages of a continued and integrated study of these two sacrificial systems based on the zooarchaeological evidence.